Kwestia marokańska w dyplomacji Théophile a Delcasségo (1898-1905) - Olejnik, Edyta (Acta Universitatis Lodziensis. Folia Historica, 2008)
At the end of 19th Century, after the Fachoda crisis in French and British diplomacy, French colonialists conceived the notion to move forward in Morocco. As there was no more hope for reopening the Egyptian question, Morocco could have been a reasonable compensation for humiliation in Fachoda. France had for a long time been engaged in the Maghreb region - it had occupied Algeria in 1830 and Tunisia in 1881. Morocco was the only one left independent and, as the Madrid convention stated in 1880, all European countries had equal rights there. However a difficult domestic situation in Morocco and problems with Algerian warriors seeking refuge on Moroccan borders let the French interfere in this country. The Minister of Foreign Affairs in France, Thdophile Delcassd, came to a decision to eliminate the rivals that would be interested in Morocco. In 1900 he signed a treaty with Italy and drew one up with Spain in 1902 that was not ratified. Under pressure of the members of the African lobby in the Chamber of Deputies, led by Eugene fitienne, and the French ambassador in London, Paul Cambon, he started negotiations with Great Britain about the Egypt-Morocco bargain. France would leave Egypt in English hands if England accepted her rights to Morocco. The French-British agreement regulating this and some other colonial question, called the Entente Cordiale, was signed 8 IV 1904. In addition to this treaty, the Frcnch-Spanish agreement was signed. The only power interested and left behind these negotiations was Germany. Kaiser Wilhelm II, convinced by the Imperial Chancellor, Count von BUlow, decided to make a demonstration in Morocco. At the end of March 1905, he landed in Tangier, and made a speech in favor of Moroccan independence, challenging French influence in Morocco. This manifestation of German interests in Morocco caused a lot of anxiety in France. Delcassd agreed to discuss the Moroccan issue with Germany, but BUlow preferred an international conference to be called. Many French politicians were afraid that Dclcassd policy would lead to war with Germany. Prime Minister Maurice Rouvier dccided to sacrifice Delcassd to eliminate this danger. Delcassd was forced out of the ministry on 6 VI 1905. At the beginning of 1906, the international conference took place in Algeciras to settle the dispute. A free trade was decided in Morocco but Germany had to accept that France would slay the main power in this country.